An Analysis of the Conceptual and Connotative Meanings in “Yoram Gross Blinky Bill Michivious Koala” Short Story - Merina Devira (Universitas Padjadjaran, 2018)
AbstrakTujuan dari penelitian ini adalah untuk menganalisis makna konseptual dankonotatif yang terdapat pada cerita pendek Yoram Gross Blinky Bill Michivous Koala. Datadalam penelitian ini adalah kalimat-kalimat yang terdapat dalam cerita pendek tersebutyang mengandung unsur makna konseptual dan konotatif yang kemudian dianalisissecara deskriptif. Hasil dari penelitian ini menunjukkan bahwa makna konseptual yangsering ditemukan pada cerita singkat Yoram Gross Blinky Bill Michivous Koala maknayang berhubungan dengan benda (referent as entity like a thing). Serta, makna konotatifjuga ditemukan dalam cerita tersebut, khususnya konotasi kasar (hard connotation).Kata kunci: makna, konseptual, konotatif, Yoram Gross Blinky Bill Michivous KoalaAbstractThis research aims to analyse the conceptual and connotative meanings found in a short storyYoram Gross Blinky Bill Michivous Koala. Data taken in this study is sentences in which thereare elements of conceptual meanings and connotative meanings which then analysed descriptively.The data source of this research is Yoram Gross Blinky Bill Michivous Koala short story, publishedin Australia by Budget Books Pty Ltd in 1992 with 96 pages. The results of research showed thatmostly frequent conceptual meanings found in the short story of was the referent as entity like athing. Also, the words which have meanings as connotative meanings were found in the short story and the connotative meaning mostly frequent is rough connotation of them.Keywords: meanings, conceptual, connotative, Yoram Gross Blinky Bill Michivous Koala